2000
DOI: 10.1093/ageing/29.6.517
|View full text |Cite
|
Sign up to set email alerts
|

Can strategic and tactical compensation reduce crash risk in older drivers?

Abstract: fitness-to-drive screening procedures need a broader perspective to prevent an over-emphasis on procedures which focus more on deficit than on capacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…This may be due to the adoption of compensatory strategies similar to those used by elderly drivers, although there is no direct evidence of this in stroke patients (De Raedt & Ponjaert-Kristoffersen, 2000;Fisk et al, 1997;George, Clark & Crotty, 2006;Unsworth, Wells, Browning, Thomas & Kendig, 2008). Older drivers who learn and use compensatory strategies such as avoiding peak hour traffic, driving in daylight and driving only in familiar areas, can reduce their accident level to that of, or lower than, technically better drivers (De Raedt & Ponjaert-Kristoffersen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the adoption of compensatory strategies similar to those used by elderly drivers, although there is no direct evidence of this in stroke patients (De Raedt & Ponjaert-Kristoffersen, 2000;Fisk et al, 1997;George, Clark & Crotty, 2006;Unsworth, Wells, Browning, Thomas & Kendig, 2008). Older drivers who learn and use compensatory strategies such as avoiding peak hour traffic, driving in daylight and driving only in familiar areas, can reduce their accident level to that of, or lower than, technically better drivers (De Raedt & Ponjaert-Kristoffersen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The first grid is an adapted French version of Test Ride for Investigating Practical fitness to drive (TRIP) [60,61]. This grid assessed eleven dimensions of driving: vehicle position on the road, vehicle tracking, speed, visual behavior, road signs, overtaking, anticipatory reactions, communication with other road users, exposure to specific situations (such as left-turn or dual carriageway), vehicle handling, general impressions of the instructor.…”
Section: Test Ride For Investigating Practical Fitness To Drive (Trip)mentioning
confidence: 99%
“…Each of these dimensions was evaluated as: insufficient, doubtful, sufficient, good or not applicable. The driving instructor completed this grid at the end of the course, which led to an overall score out of 100 points, and to three sub-scores: the tactical sub-score, out of 46 points, which takes into account speed and safety distance choices made by the driver; the tactical compensation sub-score, out of 20 points, which reflects the behavioral adaptation of the driver depending on the traffic situation and road design, and finally, the operational sub-score, out of 39 points, which considers vehicle handling and mechanical operations by the driver [61].…”
Section: Test Ride For Investigating Practical Fitness To Drive (Trip)mentioning
confidence: 99%
“…Specifically, numerous researchers have shown that visual motion processing relates to accident risk and/or driving performance (Conlon and Herkes, 2008;De Raedt and Ponjaert-Kristoffersen, 2000;Raghuram and Lakshminarayanan, 2006;Wood et al, 2008). As well, numerous visual perception investigators have demonstrated age-related deficits in contrast sensitivity for stationary low spatial frequency sine wave gratings in peripheral vision (Schefrin, Tregear, Harvey and Werner, 1999), drifting or counter-phase flickering low spatial frequency gratings in central vision (Owsley, Sekuler and Siemsen, 1983;Sekuler and Hutman, 1980;Sekular, Hutman and Owsley, 1980), and coherence thresholds for random dot stimuli drifting in peripheral and central vision at a retinal velocity similar to that of the driving environment (Atchley and Anderson, 1998).…”
Section: Introductionmentioning
confidence: 99%